2021
DOI: 10.1037/apl0000860
|View full text |Cite
|
Sign up to set email alerts
|

Plug back into work, safely: Job reattachment, leader safety commitment, and job engagement in the COVID-19 pandemic.

Abstract: With many employees returning to work after lockdowns and quarantines in the current COVID-19 pandemic, research that seeks to identify effective ways to help them regain focus at work is warranted. However, the small body of applied psychology literature on large-scale disruptive events has paid insufficient attention to this important topic. Further, different from acute events (e.g., disasters), the ongoing pandemic poses an additional challenge for organizations as they seek to effectively protect employee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 48 publications
3
77
1
2
Order By: Relevance
“…For instance, a recent study by Fu et al (2021) found that the anxiety levels of the employees are affected by the reported number of COVID-19 cases and the acceleration and velocity at which the reported number is changing, thus affecting the employees' work functioning (engagement, performance, and emotional exhaustion). However, fewer studies have looked at what constitutes effective leadership in the workplace during such a crisis and its potential antecedents (e.g., Hu et al, 2020;Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a recent study by Fu et al (2021) found that the anxiety levels of the employees are affected by the reported number of COVID-19 cases and the acceleration and velocity at which the reported number is changing, thus affecting the employees' work functioning (engagement, performance, and emotional exhaustion). However, fewer studies have looked at what constitutes effective leadership in the workplace during such a crisis and its potential antecedents (e.g., Hu et al, 2020;Yuan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, occupants returning to their offices will most likely require that their employers provide a workplace favorable for their health and wellbeing. With the continuation of the COVID-19 pandemic, current investigations are exploring the actions employers are willing to take to protect employees' health [33]. In light of these possible changes, our comfort map's relevance is obvious, since the mapping of IEQ parameters can be supplemented with other parameters that jointly influence the development of a healthy and safe work environment and enhance occupants' wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…If workers feel there is an age diversity practice in their organization, it will most likely invest more energy and effort into doing their job, and be more engaged and fully concentrated in the job. Yuan et al, (2021) indicate that age diversity was positively associated with organizational performance through the mediation of increased human and social capital. In addition, functional diversity and age-inclusive management amplified the positive effects of age diversity on human and social capital.…”
Section: Can Age Strengthen Psychological Capital Relationships and Employee Work Engagement?mentioning
confidence: 94%